Repellent action of neem (azadirachta indica) seed oil cream against anopheles gambiae mosquitoes (2009)
This paper conducted an evaluation of repellent effect of neem seed oil formulated in a vanishing type cream base against Anopheles gambiae mosquito under laboratory conditions using human volunteers. The seed oil was extracted and then prepared in five different concentrations of 0, 2.5, 5.0, 7.5 and 10.0% w/w respectively in a vanishing cream base. A commercially available repellent Deet was used as control. The result shows that concentrations 2.5, 5.0, 7.5, and 10.0% w/w and Deet (control) all repelled night-biting Anopheles gambiae mosquitoes at three consecutive 10mins interval for every 5-min exposure time. The duration of protection of various concentrations of neem seed oil cream and control (Deet) was of the order 10.0% > Deet> 7.5%> 5.0% >2.5%.The present study demonstrates potential of neem seed oil cream as mosquito repellent particularly at higher concentrations of 7.5 and 10.0%w/w respectively. This finding may lead to new and more effective strategies for protection from and control of mosquitoes.